Modeling of dust particles canting as input to microwave cross polarization - Musa, A.; Camara, Mamadi Fara; Hassan Abdalla Hashim, Aisha; Bashir, Saad Osman; Hamed, Sameir M. Ali (IEEE, 2015)
In recent time, considerable interest has been shown to electromagnetic wave propagation in arid regions and the influence of sand and dust storms with emphasis on signal attenuation and cross polarization in dual polarized systems for frequency spectrum conservation. The realization of a dual-polarized system is, however, usually limited by degree of cross polar discrimination that can be achieved between the two orthogonal channels. Aside from non-sphericity of falling dust particles, cross polarization has been attributed to tendency of the falling particles to align in a particular direction (canting angle). While dust particle shape is yet to be well tackled, the existing works on cross polarization have only succeeded in guessing the canting angle. To this end, this work explicitly deals with modelling and calculations of canting angle as input to the cross polarization discrimination by considering the forces influencing orientation of the falling particle and use of turbulence shear and inertial torque. Results of the proposed model compared with some published results show close agreement.